FEASIBILITY STUDY OF GROUND ENHANCEMENT MATERIAL (GEM) PRODUCTION STARTUP AS AN IMPORT SUBSTITUTION BASED ON TECHNOLOGICAL AND FINANCIAL ASPECTS - Jakah, Jakah; Priswantoro, Andis; Farakhan, Putra Zaki; Syah, Herwin; Sumarnadi, Eko Tri; Herawan, Wawan (Jurnal Rekayasa Mesin, 2024)
Ground Enhancement Material (GEM) plays a crucial role in lightning protection systems by effectively channeling lightning voltage into the ground. Given Indonesia's reliance on imports, it is essential to explore domestic alternatives for GEM production. This study assesses the feasibility of establishing a local GEM production startup in Tasikmalaya, West Java, based on technological and financial aspects. The analysis assumes a production capacity of 300 kg per day, an interest rate of 10%, and an economic life of 10 years. The technical aspect includes considerations such as business location, raw materials, and process/equipment technology. The financial aspect employs the Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period (PP) calculation approaches. Ensuring an adequate supply of raw materials is crucial for long-term sustainability, maintaining product quality, and managing production costs. Financially, the project yields a positive NPV value (IDR 599,655,405), an IRR exceeding the interest rate (17.9% > 10%), and a relatively short investment payback period (5 years and two months). Based on consideration of the technical and financial aspects, it is evident that the GEM production startup is a feasible and profitable investment.